2014
DOI: 10.1521/psyc.2014.77.1.86
|View full text |Cite
|
Sign up to set email alerts
|

Rejection Sensitivity and Depression: Mediation by Stress Generation

Abstract: Objective Rejection sensitivity has been found to confer risk for depression. The process through which this occurs remains unclear. This risk factor also has been associated with negative behavioral tendencies and interpersonal difficulties. Drawing on these different lines of research, the current investigation aimed to evaluate stress generation, the tendency for depression-prone individuals to experience higher rates of life stressors that are at least in part influenced by their own behavior, as a potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
46
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 43 publications
8
46
0
2
Order By: Relevance
“…Similar effects have been reported in children and adults with internalizing disorders (J. L. Allen & Rapee, 2009; Farmer & Kashdan, 2015; Hoehn-Saric, McLeod, Funderburk, & Kowalski, 2004; Kendler & Karkowski-Shuman, 1997; Kendler, Karkowski, & Prescott, 1999; Liu & Alloy, 2010; Liu, Kraines, Massing-Schaffer, & Alloy, 2014). …”
Section: Trait-state Links Inferred From Self-report and Behaviorsupporting
confidence: 82%
“…Similar effects have been reported in children and adults with internalizing disorders (J. L. Allen & Rapee, 2009; Farmer & Kashdan, 2015; Hoehn-Saric, McLeod, Funderburk, & Kowalski, 2004; Kendler & Karkowski-Shuman, 1997; Kendler, Karkowski, & Prescott, 1999; Liu & Alloy, 2010; Liu, Kraines, Massing-Schaffer, & Alloy, 2014). …”
Section: Trait-state Links Inferred From Self-report and Behaviorsupporting
confidence: 82%
“…For instance, Gibb and colleagues (2001) found that childhood emotional maltreatment predicted cognitive vulnerability and hopelessness, which in turn led to increases in depression. Additionally, negative self-associations, fear of criticism, and maladaptive interpersonal schemas also have been found to mediate the relationships between childhood emotional maltreatment and depression in adulthood (Harmelen et al, 2010; Liu et al, 2014; Wright, Crawford, & Del Castillo, 2009). Specifically, interpersonal schemas of shame and vulnerability to harm were found to mediate the relationship between childhood emotional abuse and neglect and subsequent depressive symptoms (Wright et al, 2009).…”
Section: Emotional Clarity As a Mechanism Linking Emotional Neglect Amentioning
confidence: 99%
“…Moreover, coping styles can predict depression (Nakano, ). Also, coping styles are often viewed as mediating role (Liu, Kraines, Massing‐Schaffer, & Alloy, ; Nakano, ). A cross‐sectional study explored the mediating role of coping styles in the relationship between psychological capital and burnout among Chinese nurses (Ding et al., ).…”
Section: Introductionmentioning
confidence: 99%